Biochemical Studies of Caryophyllidean Tapeworms in Fresh Water Fish Clarias batrachus - Sunita Borde, Sushil Jawale, Asawari Fartade and (Recent Research in Science and Technology, 2011)
Parasitic biochemistry has great practical importance through chemotherapy and vaccine production and in understanding of the complex association involved in the host parasite relationship However; information in parasite biochemistry is patchy. Caryophyllidean cestodes are the most pathogenic parasites in fresh water fish Clarias batrachus in tropic and sub tropic areas. Present investigation deals with the biochemistry (Protein, glycogen, lipid) of Caryophyllidean parasites in fresh water fish Clarias batrachus.